Simlandscape, a design and research support system for local planning, based on the scenario method and Parcel-Based GIS - Robert S. De Waard (European Regional Science Association (ERSA), 2005)
Many authors mention gaps between planning and reality (Salet, 2000; Wheeler, 2002), modelling and reality (Parker, 2003), and between modelling and planning (Clark, 2003). The first gap refers to inadequate planning models and instruments and the second one to the yet inadequate simulation models. The last before mentioned gap refers to cultural and ontological differences between these fields. There seems to be a kind of hate-love relationship: there is a promise of synergy, but also a considerable communication problem. Inside planning there is an ongoing debate on what qualities are important, how to deal with stakeholders and how to implement plans. This debate stretches from the functionalistic modernism to identity oriented comprehensive new regionalism. Planning concepts are in essence instruments for governance and therefore developed for and focused on control and intervention of specific aspects of spatial development. The root of planning is about the creation of the future and not about future research. This focus is one of the reasons why so many regional plans fail to be implemented. Modelling is focused on system behaviour; it is focused on scientific future research. Through its scientific approach and still inapt models, modelling however generates results that many planners do not recognize as practical from their daily perspective. They mistrust the models and find their grid based maps primal. Planning and modelling are complementary and therefore in principle synergetic. Modelling could provide planning, its context and moneylender, with a powerful evaluation tool. For this to happen however planning has to be more open to landscape as an autonomous system and must develop consistent (scenario) approaches. Now, planning models are mostly not adequate for interactive scenario development and simulation. And modelling has, next to improving performace, to pay more attention to practical planning issues (spatial quality and practise data) and language (catographic products and scales). This way they could make a beautiful couple, provided they work on themselves. What is required is a kind of intermediate or integrative scenario and typology approach. Simlandscape is a methodological toolbox for land use planning. It includes research and development, evaluation and monitoring of panoramic land use scenarios. It has been specifically developed to do the before mentioned job. Simlandscape was the object of a recently finished R&D project. It is designed to accommodate future research and interactive scenario development (explorative interactive planning) on a local and regional scale. The toolbox is based on an ontological transformation model of how landscape changes. Key elements are that Simlandscape is parcel based and actor and object orientated. The innovative aspects of Simlandscape have to do with the effect of the key elements of the model – an integration of land property and –exploitation in a landscape layer model in combination with a cadastral data model - for the comprehensiveness of the tool with respect to research activities, plan phases, qualities and stakeholders.
Keywords: 330